PENGARUH MOTIVASI KERJA DAN KOMPETENSI GURU TERHADAP KINERJA GURU MODERASI SUPERVISI KEPALA SEKOLAH ( Studi pada Guru SMPN Sub Rayon 4 Kota Semarang ) (Jurnal Mahasiswa Pasca Sarjana, 2015)
The  objective  of  the  study is to evaluate  the  influence  of  working  motivation  and  teachers competence on to the teachers performance  moderated  and supervised by the principal ( research on teachers of  SMPN  Sub  Rayon  4 Semarang ). Kind  of  the study is  using  explanatory  Reseaach. The  population  of  the study  are  the  teachers of  SMPN  Sub Rayon 4  Semarang. The  number  of the  respondent  is 168  people.The sample taken by census technique. The technique of data analysis  is  using  linear  regression  analysis  model  testing , R2  test and F test. The  hypothesis  test using  t test  and  moderation  test. Based on the study result, the  cunclusions are : (1) Working motivation positively does not  effect teachers performance significantly, (2) Teachers  competence  effects the  teachers performance positively, (3) Principal  supervision effect the teachers performance significantly and positively, (4) Principals supervision moderates the relation  between  working  motivation and  teachers  performance, (5) Principal  supervision  does  not  moderate the  effect of teachers  competence  to  teachers performance. Key Word : Motivation,  Competence , Supervision , and  Performance.